Spatial dimensions in Roman wall painting and the interplay of enclosing and enclosed space: a new perspective on second style - Dietrich, Nikolaus (Arts, 2019)
This article engages with the interplay of two-dimensional and three-dimensional wall decoration in Roman wall decoration of the so-called four Pompeian styles. Instead of describing the rapid changes in the use (or non-use) of techniques for creating perspectival depth in August Mau’s four styles within an autonomous development of decorative principles, either favoring surface over depth, or vice versa, this article will discuss the imaginary space/surface on the walls in relation to the ‘real’ space enclosed by the decorated walls and—foremost—their inhabitants as the actual referent of the decoration. The discussion will focus on second-style wall decoration, with glimpses on the earlier first and later third and fourth styles in a final section.
Gesehen am 16.09.2019